2023
DOI: 10.3389/fevo.2022.1104369
|View full text |Cite
|
Sign up to set email alerts
|

Variations and influencing factors of soil organic carbon during the tropical forest succession from plantation to secondary and old–growth forest

Abstract: IntroductionSoil organic carbon (SOC) accumulation changed with forest succession and hence impacted the SOC storage. However, the variation and underlying mechanisms about SOC during tropical forest succession are not fully understood.MethodsSoil samples at four depths (0–10 cm, 10–20 cm, 20–40 cm and 40–60 cm), litter, and roots of 0–10 cm and 10–20 cm were collected from three forest succession stages (plantation forest, secondary forest, and old– growth forest) in the Jianfengling (JFL) National Nature Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Meanwhile, we further found that forest stand age was negative correlated with bacterial diversity while positively correlated with fungal diversity (Figure 5). Decreasing bacterial diversity may result from less favourable environmental conditions, for example, increased soil acidity in older forests can reduce bacterial diversity (Lauber et al, 2009; Rousk et al, 2010; Xing et al, 2023). However, the accumulation of recalcitrant organic matter in older forests may favour fungi, which are more efficient at breaking down complex organic compounds than bacteria (Baldrian & Valášková, 2008; Boer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we further found that forest stand age was negative correlated with bacterial diversity while positively correlated with fungal diversity (Figure 5). Decreasing bacterial diversity may result from less favourable environmental conditions, for example, increased soil acidity in older forests can reduce bacterial diversity (Lauber et al, 2009; Rousk et al, 2010; Xing et al, 2023). However, the accumulation of recalcitrant organic matter in older forests may favour fungi, which are more efficient at breaking down complex organic compounds than bacteria (Baldrian & Valášková, 2008; Boer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aslan et al [49] found that the adoption of no-tillage practices could protect soil from biological degradation and maintain soil quality in comparison with that under plow tillage management. Hence, it was shown that returning farmland to forestland and grassland would provide a new environment without the disturbance of plowing for vegetation restoration, which further explains the increase in forestland SOC [48,50].…”
Section: The Influence Of Land-use Types On Soc Contentmentioning
confidence: 99%